Attaining promising efficiency through a Quasi-Solid-State symmetrical supercapacitor and Dye-Sensitized solar cell counter electrode utilizing bifunctional Nitrogen-Doped microporous activated carbon - Husain A.; Kandasamy M.; Mahajan D.K.; Selvaraj M.; Ahmad R.; Assiri M.A.; Kumar N.; Ramachandaramurthy V.K. (Elsevier B.V., 2025)
This study addresses the imperative need for high-performance and sustainable energy storage and conversion technologies by leveraging the unique properties of nitrogen-doped porous carbon (N@WnAC) derived from the waste walnut shells (WnS). In the realm of supercapacitors, the N@WnAC demonstrates remarkable performance in a three-electrode system, showcasing a high specific capacitance value of 276.7 Fg?1 at 1 Ag?1, outstanding stability (96.6 %, 5000 charge?discharge cycles) and favourable rate capability (68.8 % at 10 Ag?1). Moreover, a quasi-solid-state symmetrical supercapacitor (N@WnAC//N@WnAC) is fabricated with PVA/H2SO4 gel electrolyte, underscores outstanding performance by delivering high capacitance (126.2 Fg?1 at 0.5 Ag?1), promising rate capability (71.8 % at 5 Ag?1), favourable long-term stability (93.3 %, 5000 charge?discharge cycles), and faster charge?discharge kinetics compared to conventional counterparts. At the same time, N@WnAC//N@WnAC delivers a high energy density (42.27 Whkg?1 at 0.5 Ag?1) that was retained up to 23.96 Whkg?1 even at 5 Ag?1. Simultaneously, the study explores the potential of N@WnAC as a counter-electrode (CE) in dye-sensitized solar cells (DSSC). The obtained results underscore that unique nitrogen doping enhances the electrocatalytic activity, leading to improved electron transfer kinetics and overall cell performance. Moreover, the N@WnAC CE-based DSSC delivers a promising overall solar-to-electrical conversion efficiency of 5.84 %. ? 2024 Elsevier B.V.